Lenvatinib in combination with pembrolizumab as first-line therapy for advanced endometrial cancer: clinical case - E. A. Khachaturyan; T. G. Antonova; O. A. Stativko; I. A. Pokataev (Опухоли женской репродуктивной системы, 2025)
The combination of lenvatinib and pembrolizumab has emerged as the first non-chemo treatment for advanced endometrial cancer, particularly in cases refractory to standard therapies. This case describes the efficacy and safety of the combination of lenvatinib and pembrolizumab in the treatment of a 62-year-old patient with endometrioid adenocarcinoma who received first-line therapy with the combination of lenvatinib and pembrolizumab in the absence of repair system deficiency after adjuvant therapy. This combination offers the potential to extend survival in patients with mismatch repair proficient endometrial cancer who have received systemic neoadjuvant or adjuvant therapy.